La Pitié (1803) et La Conversation (1812) de Jacques Delille par rapport aux recherches sur la voix humaine et la parole - Bajer, Michał (Studia Romanica Posnaniensia, 2020)
The studies of Jacques Delille’s work put an emphasis on the relations between a group of poetic texts (L’homme des champs, L’Imagination, Les Trois Règnes de la nature) and their scientific intertexts. The aim of this paper is to study the scientific connotations of lesser known poems, stressing the problem of the physiological and anatomical reflections on the human voice and the speech. Is there a relation between Delille’s observations on the voice (La Pitié, p. 40, 151-152 ; La Conversation, p. 141-142, 146-147) and the terminology used by physicians or philosophers of his time? What is the impact of Rousseau’s Essai sur l’origine des langues on Delille? Is it inspiring to use the medical distinction between the physiology and the pathology to understand Delilles’s conception of the human voice?